vPERSEPSI DAN KENDALA MASYARAKAT LOKAL DALAM PENGELOLAAN DAYA TARIK WISATA PANTAI KUTA DI KABUPATEN LOMBOK TENGAH, PROVINSI NUSA TENGGARA BARAT - Simorangkir, Wahyuni Berlian Augusta; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 3 No 2 (2015): VOL 3, NO 2 (2015): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2015)
ABSTRACT This study aims to discuss the problems of local communities in the management of Kuta Beach tourist attraction as well as the perceptions of local communities in the management of his involvement in the Kuta Beach tourist attraction. The purpose of this study is to determine the constraints faced by local communities in the management of Kuta Beach tourist attraction as well as public perceptions in the involvement of the management of Kuta Beach tourist attraction. The anticipated benefits of this research are the benefits of academic and practical benefits. In achieving the objectives of the study, used a qualitative descriptive method to conduct a review directly to Kuta Beach in the village of Kuta, Central Lombok regency. The technique of collecting data using interviews with several informants and questionnaires to local communities related to the theme in question, and supported by literature study of previous reports. To obtain information use informers determination technique using key informants and respondents determination techniques by means of proportional random sampling. From the analysis, there are several kinds of constraints which lead to a lack of role of local communities in the management of Kuta Beach tourist attraction such as the low quality of human resources and the lack of government attention in improving the quality of human resources. And note also the perception of the local communities as stakeholders in tourism in Kuta Beach that they really want the training and education about the management of a tourist attraction. Advice can be given to increase the role of local communities in the management of Kuta Beach tourist attraction include the active role of local government in improving the means of education, outreach activities promoting tourism and business management training to the business community as the perpetrator of tourism. Besides, the government's focus on improving the welfare of local communities so that people are more optimally excited to be involved in the management of Kuta Beach tourist attraction.
Keywords: Perception, constraint management